Knowledge and Practices of HealthCare Workers Regarding of Medical Waste Management in Hospitals of Al Najaf Governorate - Naseem B. Saadoon,; H.Ali, Luma; A. Kadum, Suha (Journal of Techniques, 2022)
Medical waste (MW) is a serious problem in many developing countries. Iraq being one of them it faces challenges in waste management due to the environmental and human health risks. This study aims to assess the knowledge and practices of healthcare workers on medical waste management and determine the relationship between socio-demographic characteristics of healthcare workers with knowledge and practices. A descriptive; cross sectional study conducted at Al-Najaf governorate hospitals. It includes 443 participants collected during the period of 2nd January until 31th March 2022 using a structured questionnaire which depends on the National Guide to Infection Control in the Iraqi Health Institution and the previous studies. 443 participants with the mean ± SD of their ages was 29.18 ±7.68 years, female was represented (58.9%). The highest percentage of the studied samples were paramedical staff (70%), had Baccalaureate certification (44%), period of experience (1-5) years (62.98%). The majority of them (69.1%) did not undergo any training program. In general, knowledge about MWM is fair (69.9%), good (25.1%) and (4.9%) poor, while about practices, (38.6%) had poor practices, (38.6%) fair, (25.1) good. This study concluded that healthcare workers in Al-Najaf hospitals had fair knowledge and practices about Medical Waste Management.